Early Immunoglobulin Therapy and Outcomes in Kawasaki Disease. Issue 39 (September 2015) - Ho, Chi-Lin; Fu, Yun-Ching; Lin, Ming-Chih; Jan, Sheng-Ling; Zhu., Meihua
<x xml:space="preserve">Abstract</x> Abstract Kawasaki disease is the leading cause of acquired heart disease among children in most industrialized countries; however, only few descriptive studies have discussed the pros and cons of early immunoglobulin therapy. This study aimed to see the effect of early immunoglobulin therapy on Kawasaki disease outcomes. Patients who received immunoglobulin therapy for the first time were enrolled. Basic data were analyzed for descriptive epidemiology. If there was no prescription of antipyretics 4 to 12 days before admission, those patients were regarded as early immunoglobulin therapy group. The risk for acute aneurysm, requiring long-term anticoagulant therapy and recurrence rate were compared. Of 5235 patients with first attack of Kawasaki disease, 1156 received early immunoglobulin therapy. The odds ratios for acute aneurysm and needing long-term anticoagulant therapy were 0.99 (95% confidence interval [CI], 0.75–1.29) and 1.06 (95% CI, 0.86–1.31), respectively. The recurrence rate was higher for the early immunoglobulin therapy group, with an adjusted hazard ratio of 1.38 (95% CI, 1.29–1.47). Early immunoglobulin therapy might not be beneficial for the coronary outcomes of children with Kawasaki disease in this observational study. On the contrary, it might be associated with higher recurrence rate. A randomized controlled study comparing early and late intravenous immunoglobulin therapy would have probably brought relevant results.